2003
DOI: 10.1001/archotol.129.9.1010
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Lingual Tonsil Hyperplasia

Abstract: Clinically significant lingual tonsil hypertrophy is a rare entity in children. We describe a child, status postadenotonsillectomy, with recurrent hypertrophy of the lingual tonsil after carbon dioxide laser ablation. Workup was negative for immunodeficiency, cystic fibrosis, and allergies. The findings of examination of multiple biopsy specimens of the tissue suggested follicular hyperplasia, and cytometery showed no evidence of a lymphoproliferative disorder. Empiric treatment with a histamine2-receptor bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…In contrast, lingual tonsillar hypertrophy has been associated with obstructive sleep apnea and acute airway obstruction, as well as dysphagia and foreign body sensation . Cough has been mentioned in some reports that detail lingual tonsillitis, but usually as a secondary diagnosis or mentioned among a constellation of symptoms . Albeit, Lewis et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, lingual tonsillar hypertrophy has been associated with obstructive sleep apnea and acute airway obstruction, as well as dysphagia and foreign body sensation . Cough has been mentioned in some reports that detail lingual tonsillitis, but usually as a secondary diagnosis or mentioned among a constellation of symptoms . Albeit, Lewis et al .…”
Section: Discussionmentioning
confidence: 99%
“…This structure is responsible for a wide range of pharyngeal symptoms and the diagnosis of this pathology may easily be obtained with an accurate clinical history and examination of the area with endoscopes. Lingual tonsillitis can be treated with the same medications that are used for the more common forms of palatine tonsillitis (Figure ). Surgery should be considered only in cases of failure of the medical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, gastroesophageal reflux disease may have played a secondary role in pathogenesis. One prospective study [16] showed enlargement of the lingual tonsil in 70% of patients who had a diagnosis of gastroesophageal reflux disease, and one hypothesis is that treatment with antireflux medication aids resolution of recurrent lingual tonsil hyperplasia [17]. In patients with a TGDC and upper aerodigestive tract symptoms, direct or flexible endoscopic examination is warranted before surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…33 Parham reports on a pediatric patient with recurrent LTH, who was successfully treated with histamine 2 -receptor blockers with no recurrence of LTH after one year. 34 Thus, risk factors for LTH, in pediatric patients, seem to include Down's syndrome, prior tonsillectomy and/or adenoidectomy and gastroesophageal reflux.…”
mentioning
confidence: 99%